الشفافية والمسائلة كآلية للحد من الفساد في الجماعات المحلية - علي ،مسعودي; ربيحة ،فزاعي (جامعة الوادي University of El Oued, 2024)
تهدف هذه الدراسة، التي تحمل عنوان "الشفافية والمساءلة كآلية للحد من الفساد في الجماعات المحلية"، إلى استكشاف دور الشفافية والمساءلة في مكافحة الفساد على مستوى الجماعات المحلية. بحيث، تقدم استعراضًا شاملاً لأهمية الشفافية والمساءلة كوسيلتين رئيسيتين في محاربة الفساد في سياق الجماعات المحلية، ويبدأ الفصل الأول بتحليل مفهوم الفساد الإداري ومظاهره وأسبابه وآثاره، مما يوفر فهمًا شاملاً للسياق الذي تنشأ فيه الاحتياجات للشفافية والمساءلة. ثم ينتقل الفصل الثاني إلى دراسة دور الشفافية والمساءلة في تحديد الفساد والحد منه، مع التركيز بشكل خاص على القوانين المحلية كقانون البلدية والولاية وكيفية تطبيق مبادئ الشفافية والمساءلة في هذه السياقات. ويتضح من خلال الدراسة أن تعزيز الشفافية وتعزيز ثقافة المساءلة يمكن أن تكون آليات فعالة للحد من الفساد في الجماعات المحلية، مما يسهم في تحسين الإدارة المحلية وبناء مجتمع أكثر شفافية ونزاهة. This study, titled "Transparency and Accountability as Mechanisms to Combat Corruption in Local Communities," aims to explore the role of transparency and accountability in combating corruption at the local community level. It provides a comprehensive overview of the importance of transparency and accountability as two key tools in the fight against corruption in the context of local communities. The first chapter begins with an analysis of the concept of administrative corruption, its manifestations, causes, and effects, thus providing a comprehensive understanding of the context in which the need for transparency and accountability arises. The second chapter then moves on to study the role of transparency and accountability in identifying and mitigating corruption, with a particular focus on local laws such as municipal and state laws, and how the principles of transparency and accountability are applied in these contexts. The memorandum highlights that enhancing transparency and fostering a culture of accountability can be effective mechanisms for combating corruption in local communities, thereby contributing to improving local governance and building a more transparent and accountable society.
ماستر اداري